The dark-thirty Southern tales of the supernatural - McKissack, Pat 1944-; Pinkney, J. Brian (New York Knopf, 1992)
A collection of ghost stories with African American themes, designed to be told during the Dark Thirty--the half hour before sunset--when ghosts seem all too believable.
Keywords: Ghost stories, American; Horror tales, American; Afro-Americans -- Juvenile fiction; Children's stories, American; Ghosts -- Fiction; Horror stories; Afro-Americans -- Fiction; Short stories; Horror -- Fiction; Blacks -- Fiction